Exploring the Limits and Causes of Plastid Genome Expansion in Volvocine Green Algae. (8th August 2018) - Gaouda, Hager; Hamaji, Takashi; Yamamoto, Kayoko; Kawai-Toyooka, Hiroko; Suzuki, Masahiro; Noguchi, Hideki; Minakuchi, Yohei; Toyoda, Atsushi; Fujiyama, Asao; Nozaki, Hisayoshi; Smith, David Roy
Abstract: Plastid genomes are not normally celebrated for being large. But researchers are steadily uncovering algal lineages with big and, in rare cases, enormous plastid DNAs (ptDNAs), such as volvocine green algae. Plastome sequencing of five different volvocine species has revealed some of the largest, most repeat-dense plastomes on record, including that of Volvox carteri (∼525 kb). Volvocine algae have also been used as models for testing leading hypotheses on organelle genome evolution (e.g., the mutational hazard hypothesis), and it has been suggested that ptDNA inflation within this group might be a consequence of low mutation rates and/or the transition from a unicellular to multicellular existence. Here, we further our understanding of plastome size variation in the volvocine line by examining the ptDNA sequences of the colonial species Yamagishiella unicocca and Eudorina sp. NIES-3984 and the multicellular Volvox africanus, which are phylogenetically situated between species with known ptDNA sizes. Although V. africanus is closely related and similar in multicellular organization to V. carteri, its ptDNA was much less inflated than that of V. carteri . Synonymous- and noncoding-site nucleotide substitution rate analyses of these two Volvox ptDNAs suggest that there are drastically different plastid mutation rates operating in the coding versus intergenic regions, supporting the idea that error-prone DNA repair in repeat-rich intergenic spacers is contributing to genome expansion. Our results reinforce the idea that the volvocine line harbors extremes in plastome size but ultimately shed doubt on some of the previously proposed hypotheses for ptDNA inflation within the lineage.